A Morphometric Study of Adult Human Sterna from the Galloway Osteological Collection - Gonzaga Gonza Kirum; John Kukiriza; Gerald Tumusiime (Academia Anatomica International, 2020)
Background: Morphometric knowledge of the sternum is of great significance in cardiac surgery as variations in sternal dimensions have been considered a risk factor for translocation of suture material during median sternotomy, leading to poor outcomes. Fatalities attributed to subnor- mal sternal thickness have also been reported during sternal biopsies. Fractures of the sternum secondary to chest injury or cardio-pulmonary resuscitation may also be influenced by sternal thickness. Elongated xiphoid process can be mistaken for an epigastric mass which can be painful on palpation. Morphometric studies of African sterna are rare. The objective is to the study sought to describe the morphometry of adult sterna from the Galloway bone collection, Makerere University, Kampala, Uganda. Subjects and Methods: This study employed a descriptive cross sectional design to collect and analyze quantitative data. Eighty five dry adult sterna (75 males and 10 females) were examined at the Department of Human Anatomy, Makerere University. Data analysis at univariate and bivariate levels were performed using SPSS version 21.0 statistical software. Results:A significant difference in the average length of the mesosternum was found between males at 94.6 mm (SD 11.2) and females at 82.2 mm (SD 15.2) (P=0.002). Two cases (9.5%) presented with elongated xiphoid process and one (1.2%) with subnormal mesosternal thickness. Conclusions: Our study highlights the importance of knowledge of the sternal morphometry in sex identification, physical examination, sternal puncture and other thoracic procedures, calling for increased awareness of the findings.